Czytanie w łóżku. Lektura jako atrybut atrakcyjności w kampaniach promujących czytelnictwo - Bałaga, Małgorzata (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2014)
The article is an attempt to analyse campaigns to promote reading, including You don’t read? I won’thave sex with you, Read – pick-up, or Naked girl reading, and related concepts aiming to present a book and the very act of reading as a new attribute of attractiveness. The main aim of such initiatives is primarily a presentation of the book as a "sexual attribute" and to demonstrate the relationship between reading and intellectual attractiveness. Campaigns designed in that way, aimed at "sexualisation of literature", provoke a question about the effectiveness of such projects. The process of reading is subject to all kinds of fashions, and analysing such promotional campaigns reveals the modern reader profile and his or her reading needs, as well as the relationship between reading choices and image creation.